Conocimientos y prácticas sobre formas de prevención de ITS/VIH-sida en los/las estudiantes de bachillerato del colegio fiscal mixto nocturno Manuel Enrique Rengel de la ciudad de Loja periodo diciembre 2012 - octubre 2013. - Rodríguez Reinoso, Dilma Esperanza (2013)
STI are a public health problem with an increasing percentage of the epidemiological profile of developing countries and even in industrialized countries , given the problems at global, national and local levels has proposed to develop this research called " kNOWLEDGE AND PRACTICES ON WAYS OF PREVENTING STI / HIV-AIDS IN THE/THE BACHELOR OF COLLEGE STUDENTS NIGHT MIXED FISCAL RENGEL MANUEL ENRIQUE LOJA CITY PERIOD DECEMBER 2012 -OCTOBER 2013 " , considering the following objectives : To determine the knowledge STI / HIV - AIDS, which have the/the high school students of mixed tax College Manuel Enrique Rengel , identify preventive practices for STI/HIV-AIDS, which are observed in the /the high school students in the school under study, meet participation of the educational institution concerning sexual education promote high school students of the College prosecutor Manuel Enrique Rengel mixed city of Loja. From a descriptive study on a sample of 109 students who were surveyed timely , emphasizes that students have a good level of knowledge about STI and HIV/AIDS , as evidenced by a 35.8 % state that having multiple partners is the main cause of infection , 29.4% for non-use of condoms , a 21.1 % corresponds to all of the above and 13.7 % say it is the drug , in terms of preventive practices for STI/HIV- AIDS, shows that 75.2 % practice fidelity , 24.8 % do not consider fidelity as a preventive practice , 77.1 % make sexual abstinence , and 22.9 % has not been done on the use of condoms 56% did not use condoms during sex and 44 % when used as preventive practice .  At the institutional level there is little contribution to promote sexual education of their students, no study in the curriculum of an educational program related to STI/HIV-AIDS.